2020
DOI: 10.1136/neurintsurg-2020-016216
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular systolic dysfunction is associated with poor functional outcomes after endovascular thrombectomy

Abstract: BackgroundEndovascular thrombectomy (ET) has transformed acute ischemic stroke (AIS) therapy in patients with large vessel occlusion (LVO). Left ventricular systolic dysfunction (LVSD) decreases global cerebral blood flow and predisposes to hypoperfusion. We evaluated the relationship between LVSD, as measured by LV ejection fraction (LVEF), and clinical outcomes in patients with anterior cerebral circulation LVO who underwent ET.MethodsThis multicenter retrospective cohort study examined anterior circulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…This may be explained by the shared pathophysiology between LVO strokes and ischaemic heart disease [ 24 ]. Studies have also shown that cardiac diseases, in particular LVSD, are associated with higher rates of in-hospital mortality and poorer functional outcomes [ 6 , 28 ]. This effect remains significant even after adjusting comorbidities such as age, and previous ischaemic heart disease as well as the efficacy and rate of ET.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be explained by the shared pathophysiology between LVO strokes and ischaemic heart disease [ 24 ]. Studies have also shown that cardiac diseases, in particular LVSD, are associated with higher rates of in-hospital mortality and poorer functional outcomes [ 6 , 28 ]. This effect remains significant even after adjusting comorbidities such as age, and previous ischaemic heart disease as well as the efficacy and rate of ET.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular diseases including ischaemic heart disease are common in stroke patients probably due to similar underlying comorbidities and a shared pathophysiology [ 5 ]. Left ventricular systolic dysfunction (LVSD) is often seen in patients with LVO AIS and such impaired cardiac function increases the risk of poor neurologic and functional outcomes after ET [ 6 , 7 , 8 ]. However, the role of left ventricular diastolic dysfunction (LVDD) remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Left ventricular systolic dysfunction (LVSD) has been reported as an important clinical predictor of higher morbidity and mortality in AIS patients [ 7 , 8 ]. Left ventricular ejection fraction (LVEF) is a common parameter for the evaluation of left ventricular systolic function, and is widely used in clinical diagnosis and experimental research [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Left ventricular ejection fraction (LVEF) is a common parameter for the evaluation of left ventricular systolic function, and is widely used in clinical diagnosis and experimental research [ 9 11 ]. Previous studies prior to IVT or ET have indicated that reduced LVEF was associated with higher NIHSS scores at admission, poorer functional outcomes and higher in-hospital mortality rates [ 8 , 12 ]. LVSD may involve in the pathophysiology of AIS through different mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Special attention dedicated to patients suffering from cancer, whose immune system is compromised either due to treatment or disease itself (6). As such many health care systems have been overwhelmed with depression and anxiety (7). There is a potential shortage in physical resources, such as ventilators, needed to care for surges of critical ill patients (8).…”
Section: Introductionmentioning
confidence: 99%